Study on the rheological properties of nano-SiO2 composite modified basalt mineral fiber asphalt mortar - Haiwei Gao; Nanxiang Zheng; Xiang Zhang; Zhihui Li; Zhuohong Cong (Materials Research Express)
To investigate the impact of mineral fiber modification and dosage on the rheological properties of fiber asphalt mastic, basalt fiber surface roughness was enhanced using nano-SiO _2 solution. Fiber asphalt mastic was prepared with a filler-bitumen ratio of 1.6 and fiber dosages of 0%, 1.3%, 2.6%, 3.9%, and 5.2%. The taper entry test, dynamic shear rheology test, and bending beam rheology test were employed to analyze the variations in taper entry, shear strength, complex modulus (G*), phase angle ( δ ), rutting factor (G*/sin δ ), modulus of strength (S), and rate of change of strength (m) of the fiber asphalt mastic. The results indicate that the optimal dosage of mineral fibers in fiber asphalt mastic is 2.6%. Nano-modified basalt fibers significantly enhance the anti-shear capacity of asphalt mastic. The high-temperature stability of fiber asphalt mastic improves with increasing fiber dosage, but the improvement becomes negligible beyond a 2.6% dosage. The interfacial bonding layer formed by asphalt on the fiber surface enhances the high-temperature performance and stress dissipation at low temperatures, thereby improving low-temperature cracking resistance.